A Research on Finance and Investment Pattern of Individualistic Women’s in Delhi City - Sangwan, Nishi; Bindu Kota, Hima (International Journal of Psychosocial Rehabilitation, 2020)
The position of women in our nation has been subject to various great changes over the past few eras. Both the frame strategies and cultural modifications gained equal opportunities for women in education, social, political, and workplace involvement. With the support of such modifications, exploitation of women to a great extent was decreased. Currently, Indian women are quite sufficient and encourage investing their savings in an appropriate way for the family's security. This research is concerned with the research of investment actions and designs followed by individualistic women in various areas of Delhi city.